Free Fatty Acids Purification in Biodiesel with Utilizing Rice Husk Silica - Muliadi Ramli; Saiful Saiful; Rahmatun Misriana (Jurnal Natural, 2013)
Silica particles had been successfully separated and extracted from rice husk by using solution of sodium hydroxides (NaOH) as solvent and were characterized with SEM-EDX. The data SEM-EDX showed that the extracted component of the rice husk contained 79,55% (w/w) of silica as the primary component. In order to understand the adsorption capacity of silica in removing free fatty acids (FFA) which were recognized as the contaminants in biodiesel., the profile of time dependence and silica amount in the adsorption process had been investigated in this study. The results indicated that the adsorption process showed optimum condition at 30 minutes with the free fatty acids (about 90,64%) of adsorption). Moreover, the adsorption capacity of silica to those impurities contaminated in biodiesel was proportional to the amount of adsorbent used in the experiment. Finally, biodiesel with less FFA was produced, and the FFA residues remained in the biodiesel were 0,58 mg/g.